Position-matching in the upper limb: professional ballet dancers perform with outstanding accuracy. - Ramsay, JR; Riddoch, M (2001)
OBJECTIVES: To investigate the accuracy in position-matching in the upper limb in two groups of subjects who were physically fit and movement aware. DESIGN: A mixed-group design was used. Objective measurement of the accuracy in position-matching at the shoulder and elbow in both dominant and nondominant arms consisted of photographic record of the position-matching test, with goniometric measurement. SETTINGS: Physiotherapy department at the Birmingham Royal Ballet and School of Health Science, University of Birmingham. SUBJECTS: Two subject groups: physiotherapy students (n = 10), professional ballet dancers (n = 10). RESULTS: A mixed design analysis of variance found significant differences between the accuracy in position-matching at both the shoulder and elbow joints in the two groups (p < 0.05), with the ballet dancers having greater accuracy then the physiotherapy students. A significant difference in the joint positions tested were demonstrated (p < 0.05) with the positions of abduction at the shoulder and extension of the elbow showing greatest accuracy in matching. There was no significant difference found between the dominant and nondominant upper limb in position-matching. CONCLUSION: Professional ballet dancers demonstrated greater accuracy in position-matching the upper limb, implying that mass and continuing practice can improve a motor sensory skill.